Pengembangan Short Video :Media Edukasi Kesehatan Tentang HIV/AIDS - Khairatun Nisa; M. Fajriannor TM; M. Hidayaturahman; Anggilia Sukma Ayu (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
One of the provinces that also contributes to the number of HIV cases in Indonesia is South Kalimantan Province. Specifically in South Kalimantan Province, the number of HIV/AIDS cases recorded until 2022 is around 3,300 cases. Around 40 percent of them come from Banjarmasin City. In 2022, there were 137 cases of HIV/AIDS recorded in Banjarmasin City. The problem that was found was the lack of interesting educational media about HIV/AIDS. This study aims to develop short videos as a health education media about HIV/AIDS. This study uses a Research and Development (RnD) research design. The data analysis technique used in this study is a quantitative descriptive analysis technique, namely by analyzing quantitative data obtained from the results of the documentary study scoring scale conducted by researchers to determine the percentage of media eligibility.The results of this study are in the form of 4 short videos with educational material containing the definition of HIV and AIDS, media and methods of transmission of HIV/AIDS, causes of HIV/AIDS and symptoms of HIV/AIDS. The average duration per video is approximately 60 seconds. The video was developed with expert assessment from the material and media aspects.The conclusion of the feasibility of developing health education media in the form of Short Video based on validation according to media experts obtained an average percentage of 95% with the category